All that glitters is not gold: authenticity and historical accuracy in representations of Mapungubwe - Andreou, Alexander (School of Architecture, Planning and Geomatics, 2023)
The (Re)Discovery of Mapungubwe in 1933 sparked an ongoing 89-year journey of interpretation, re-interpretation, hidden agendas, scientific racism and an evolution of worldviews. In being as deeply meaningful and entrenched in the South African psyche as it is, Mapungubwe features in a variety of representations. For this thesis, a selection of these representations were made of both those considered historical and contemporary. These were discussed and unpacked in accordance with the broader research question examining if their accuracy matters. In this unpacking archaeological theory is discussed, as well as the nationalist ideologies and racial science which was attributed to it in the early 20th Century. In addition to the selection of representations, a history of the re(discovery) and discoveries of Mapungubwe is also discussed. Ultimately, it does not matter if representations of Mapungubwe are accurate or authentic, as these facets are framework dependent, and have been found to each carry their own meaning or 'truth' around the Mapungubwe story.